Design of a Personalised Faceguard for an Elite Cricketer. (2015) - Kajtaz, Mladenko; Witherow, Blake; Leary, Martin; Brandt, Milan; Subic, Aleksandar
Abstract: Personalised design of a consumer product such as faceguard is dominantly semantic design as its functional component is strictly governed by safety requirements specified by the standards. This paper, which outlines activities associated with design of a personalised cricket faceguard for a prominent elite cricketer, uses earlier developed methodology to demonstrate developmental efforts and decision making processes employed in order to combine functional and affective aspects of design. Selective laser melting, an additive manufacturing technique, was employed to achieve unique designs in order to elicit instrumental and aesthetic customer's responses and allow innovation in form and structure not possible with traditional manufacturing methods.